POSITIVE FOREIGN EXPERIENCE ON ADMINISTRATIVE AND LEGAL REGULATION OF RELATIONS IN THE FIELD OF ELECTRIC POWER ENGINEERING AND DIRECTIONS OF ITS BORROWING - Миколаєць, Д. А. (Київський національний університет імені Тараса Шевченка, 2021)
Foreign experience in the processes of reforming regional electricity markets Innovation and investment development is an important and necessary component of the formation of a competitive environment, improving the efficiency of economic entities and the process of liberalization in general. The experience of foreign countries convincingly shows that the effectiveness of liberalization processes in terms of radical adaptation of legislation, stability, reliability and uninterrupted electricity supply in terms of demonopolization of the energy sector focuses on the synergetic effect, many times greater. The article examines the features of the transformation processes of the electricity markets of the leading countries of the world and Europe. A review of the criteria that formed the basis. The consequences of the mentioned reform of the regional markets of the energy sector by integrating the development of the country's industrial sector are outlined; the presence of territorial and climatic conditions, which leads to an understanding of the search for and implementation of the model that will ensure the continuity and multifunctionality of national and regional electricity markets. The stages of reform have been monitored. The implementation of the regulatory framework was focused on the vectors of its implementation: the delimitation of certain activities related to the transportation, production, purchase and sale of electricity; unification of the single tariff for the use of energy resources in all EU territories. It was found that in the process of reforming the electricity markets there is no universal scenario that could accelerate these processes, as the transformation is carried out only under special conditions specific to a particular country. The experience of these developed countries has shown the ambiguity of the consequences of reform under the application of the same models. It is noted that in the process of liberalization of energy markets, the countries of the European Union primarily aimed to implement legal documents and structurally divided them for the entire period of reforms into 3 stages. The future scenario of reforming the electricity market of Ukraine is outlined, taking into account the experience and experience of leading countries with an emphasis on such segments as: “the market of direct bilateral agreements”; "Futures market", "balancing market", "related market". The reform of the branch, structural support was monitored. The measures to be implemented for the reform of the electricity market in 4 groups were systematized: normative-legal, organizational-structural, financial-investment, technical-innovative measures.

Досвід зарубіжних країн переконливо свідчить, що результативність процесів лібералізації за умов докорінної адаптації законодавчо-нормативного забезпечення, стабільності, надійності та безперебійності електропостачання за умов демонополізації енергетичної сфери орієнтується на синергетичний ефект, більший у рази. У статті досліджено особливості трансформаційних процесів електроенергетичних ринків провідних країн світу та Європи. Здійснено огляд критеріїв, які лягли в основу. Окреслено наслідки зазначеного реформування регіональних ринків енергетичного сектора шляхом інтеграції розвитку промислового сектора країни; наявність територіально-кліматичних умов, що веде до розуміння пошуку та імплементації саме тієї моделі, яка якнайбільше забезпечуватиме безперебійність і багатофункціональність національних і регіональних електроенергетичних ринків. Здійснено моніторинг етапів реформування. Імплементація нормативно-законодавчих засад була орієнтована в напрямі векторів своєї реалізації: розмежування певних видів своєї діяльності, пов’язаних з транспортуванням, виробництвом, купівлею та реалізацією електроенергії; уніфікація єдиного тарифу за використанням енергетичних ресурсів по всіх територіях ЄС. З’ясовано, що в процесі реформування електроенергетичних ринків немає універсального сценарію, котрий зміг би пришвидшити ці процеси, оскільки трансформація здійснюється виключно за особливих умов, притаманних виключно конкретній країні. Досвід приведених розвинутих країн показав неоднозначність наслідків реформування за умов застосування однакових моделей. Зазначено, що в процесі лібералізації енергоринків країни Європейського Союзу першочергово взяли за ціль імплементувати нормативно-правові документи та структурно розділили їх на весь період реформ на 3 стадії. Окреслено майбутній сценарій реформування електроенергетичного ринку України з урахуванням напрацювань і досвіду провідних країн з акцентуванням діяльності на такі сегменти, як: «ринок прямих двосторонніх договорів»; «ринок ф’ючерсних поставок», «балансуючий ринок», «супутній ринок». Здійснено моніторинг реформування галузі,структурнезабезпечення.
ПОЗИТИВНИЙ ЗАРУБІЖНИЙ ДОСВІД ЩОДО АДМІНІСТРАТИВНО-ПРАВОВОГО РЕГУЛЮВАННЯ ВІДНОСИН У СФЕРІ ЕЛЕКТРОЕНЕРГЕТИКИ І НАПРЯМИ ЙОГО ЗАПОЗИЧЕННЯ
Keywords: Key words: electricity markets; transformation processes; competitive environment; demonopolization of the energy sector; European Commission; regulatory regulation.; Ключові слова: електроенергетичні ринки; конкурентне середовище; демонополізація енергетичної сфери; Європей-ська Комісія; нормативно-правове регулювання.